2013
DOI: 10.1002/adem.201300057
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Metallic Hollow Sphere Structures

Abstract: Metal hollow spheres (MHS) and metal hollow sphere structures are special types of cellular metals with an enormous application potential in structural and functional applications. A lot of effort has been made during the last two decades in order to develop the manufacturing process and to investigate the properties of this type of structure. Additional functionalizing of MHS is possible by filling the spheres with ceramic powders or phase change materials. Furthermore, by coating the spheres with different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Also, it has been reported that the heat capacity of the MHS can be significantly increased by filling the spheres with phase change materials [99]. MHS filled with phase change materials are useful, for example for designing fast working heat exchangers or thermal storage systems.…”
Section: Hybrid Wire-woven Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been reported that the heat capacity of the MHS can be significantly increased by filling the spheres with phase change materials [99]. MHS filled with phase change materials are useful, for example for designing fast working heat exchangers or thermal storage systems.…”
Section: Hybrid Wire-woven Metalsmentioning
confidence: 99%
“…Additional functionalizing of MHS is possible by filling the spheres with ceramic powders or phase change materials. The vibration damping can be increased by more than one order if the closed cells are filled with floating powders such as ceramics [98,99]. Consequently, particle filled spheres can be used for vibration damping and stiffening of machine parts, in automotive and other applications.…”
Section: Hybrid Wire-woven Metalsmentioning
confidence: 99%
“…Jehring has also investigated the influence of mass ratio, particle size distribution, and cavities size on vibration attenuation [33]. Goehler et al [34] have replaced the conventional steel sheets of a milling slide with particle-filled hollow sphere sandwiches to reduce the vibration amplitude. The authors have shown that in comparison to the conventional approach, the particle-filled metal hollow spheres approach increases the damping by factor 5.…”
Section: Application Of Particle Dampersmentioning
confidence: 99%
“…The metal hollow sphere composites (MHSCs) belong to the special metal hollow spheres structures, and the acoustic properties of the MHSCs are worthy of study. Owing to the special structures of the MHSCs, the MHSCs have a series of advantageous mechanical properties and functional characteristics, such as low density [14,15], high specific strength [16], high energy absorption [17][18][19][20][21][22][23][24], heat insulation [25], nuclear shielding [26][27][28], and ballistic performance [29,30].…”
Section: Introductionmentioning
confidence: 99%